Von Matisse bis Dali - Das Legat Georges F. Keller an das Kunstmuseum Bern - Kunstmuseum Bern, Bern; Cooper, Douglas; Göpel, Erhard; Hart, Henry; Honeyman, Tom J.; Hubert, Ernest; Huggler, Max; Kuthy, Sandor; Oberlé, Jean; Ozenfant, Amédée; Stooss, Toni; Wagner, Hugo (Bern : Kunstmuseum Bern, 1998)
Berard, Christian ; Cézanne, Paul ; Dali, Salvador ; Degas, Edgar ; Delaunay, Robert ; Delaunay, Sonia ; Derain, André ; Despiau, Charles ; van Dongen, Kees ; Dufy, Raoul ; de Forbin, Auguste ; Giacometti, Alberto ; Girard, André ; Guino, Richard ; Hackert, Philipp J. ; Hubert, Ernest ; Koch, John ; Fresnaye, Roger de la ; Lamotte, Bernard ; Lurçat, Jean ; Manet, Edouard ; Masson, Andre ; Matisse, Henri ; Modigliani, Amedeo ; Ozenfant, Amédée ; Peyrissac, Jean ; Picabia, Francis ; Picasso, Pablo ; Renoir, Auguste ; Rodin, Auguste ; Rouault, Georges ; Rousseau, Henri ; Sicard, Pierre ; Soutine, Chaim ; Utrillo, Maurice
biografie
Von Matisse bis Dali - Das Legat Georges F. Keller an das Kunstmuseum Bern / De Matisse à Dali : Le Legs Georges F. Keller au Musée des Beaux-Arts de Berne, Kunstmuseum Bern, 26.6. - 4.10.1998
Duits
Duits & Frans
Frans
boek